Developmental regulation of protein interacting with C kinase 1 (PICK1) function in hippocampal synaptic plasticity and learning - Volk, Lenora; Kim, Chong-Hyun; Takamiya, Kogo; Yu, Yilin; Huganir, Richard L. (NATL ACAD SCIENCES, 2010)
AMPA-type glutamate receptors (AMPARs) mediate the majority of fast excitatory neurotransmission in the mammalian central nervous system. Modulation of AMPAR trafficking supports several forms of synaptic plasticity thought to underlie learning and memory. Protein interacting with C kinase 1 (PICK1) is an AMPAR-binding protein shown to regulate both AMPAR trafficking and synaptic plasticity at many distinct synapses. However, studies examining the requirement for PICK1 in maintaining basal synaptic transmission and regulating synaptic plasticity at hippocampal Schaffer collateral-cornu ammonis 1 (SC-CA1) synapses have produced conflicting results. In addition, the effect of PICK1 manipulation on learning and memory has not been investigated. In the present study we analyzed the effect of genetic deletion of PICK1 on basal synaptic transmission and synaptic plasticity at hippocampal Schaffer collateral-CA1 synapses in adult and juvenile mice. Surprisingly, we find that loss of PICK1 has no significant effect on synaptic plasticity in juvenile mice but impairs some forms of long-term potentiation and multiple distinct forms of long-term depression in adult mice. Moreover, inhibitory avoidance learning is impaired only in adult KO mice. These results suggest that PICK1 is selectively required for hippocampal synaptic plasticity and learning in adult rodents.
Keywords: LONG-TERM DEPRESSION; AMPA-RECEPTOR TRAFFICKING; IONOTROPIC GLUTAMATE RECEPTORS; DOMAIN-CONTAINING PROTEINS; MGLUR-DEPENDENT LTD; BINDING-PROTEIN; IN-VIVO; METABOTROPIC GLUTAMATE-RECEPTOR-7; EXCITATORY SYNAPSES; PKC PHOSPHORYLATION